INTEGRATING DIGITAL PAINTING TOOLS TO ENHANCE STUDENTS’ VISUAL LITERACY IN FINE ARTS EDUCATION - Muzafarova Sanobar Murodullayevna (НАУЧНЫЕ ИССЛЕДОВАНИЯ И ИННОВАЦИИ, 2025)
Abstract: This article explores the integration of digital painting tools in fine arts education to enhance students’ visual literacy. It examines how interactive software, digital platforms, and multimedia resources contribute to developing students’ compositional skills, aesthetic understanding, and creative problem-solving. The study emphasizes the importance of teacher guidance, project-based activities, and collaborative learning in creating an engaging environment that promotes both individual and group creativity. Additionally, the article highlights the role of continuous assessment and feedback in supporting students’ artistic growth and technical mastery.